Double N-arylation reaction of polyhalogenated 4,4’-bipyridines. Expedious synthesis of functionalized 2,7-diazacarbazoles - Mohamed Abboud; Emmanuel Aubert; Victor Mamane (Beilstein Journal of Organic Chemistry, 2012)
Unusual 2,7-diazacarbazoles were prepared in one step from readily available tetra-halogenated 4,4’-bipyridines by using a double N-arylation reaction in the presence of the Pd–XPhos catalyst system. Moderate to good yields were obtained in this site-selective Buchwald–Hartwig double amination. The functionalization of these tricyclic derivatives was performed by using Pd-catalyzed cross-coupling reactions such as the Stille and Suzuki couplings. Two compounds were analyzed by X-ray diffraction and show π–π stacking involving the diazacarbazole moieties and the phenyl rings of functionalized groups.